2018
DOI: 10.1080/13573322.2018.1483908
|View full text |Cite
|
Sign up to set email alerts
|

‘Of course I ask the best students to demonstrate’: digital normalizing practices in physical education

Abstract: In this paper, we focus on the use of digital video technology for instruction in physical education (PE). Physical educators can produce PE instruction videos (PIVs) as educational resources and often use them to enable independent learning situations. Little research has focused on the criteria teachers use to select students for demonstration in such video practices, while such selections may impact the constructions of (un) desirable bodies in PE. The purpose of this study therefore was to uncover discours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Most studies identified PE teachers as the most influential mediators in defining what constituted the legitimated habitus in the playing field (Hay and lisahunter, 2006; Hay and Macdonald, 2010b). In fact, educators reinforced the traditional ideology of ability (Fitzgerald, 2005; Hay and Macdonald, 2010a, 2010b) through implicit messages and the impact of power relations on pedagogical practices (Van Amsterdam et al, 2012; Van Doodewaard et al, 2018). Hay and lisahunter (2006) explored PE teachers’ educational practices and found that the powerful messages they communicated were grounded in their own personal experiences within the movement culture.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies identified PE teachers as the most influential mediators in defining what constituted the legitimated habitus in the playing field (Hay and lisahunter, 2006; Hay and Macdonald, 2010b). In fact, educators reinforced the traditional ideology of ability (Fitzgerald, 2005; Hay and Macdonald, 2010a, 2010b) through implicit messages and the impact of power relations on pedagogical practices (Van Amsterdam et al, 2012; Van Doodewaard et al, 2018). Hay and lisahunter (2006) explored PE teachers’ educational practices and found that the powerful messages they communicated were grounded in their own personal experiences within the movement culture.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the ‘able’ student was the one who possessed idealized physicality and attitudinal dispositions informed by sport, performance and hegemonic dogmas that celebrated and valued masculine-related dispositions (Hay and Macdonald, 2010b; Hunter, 2004; Van Doodewaard et al, 2018). Physicality was contingent on dual attributes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations